Treatment of gouty lumbar spinal stenosis: a case report and bioinformatics analysis - Xiao Zhang; Wenbo Gu; Di Luo; Xi Zhu; Xusheng Li; Haifeng Yuan (BMC Musculoskeletal Disorders)
Abstract The case of Lumbar spinal stenosis (LSS) combined with tophi due to gout is rarely reported. In the course of our clinic work, we encountered a young male patient who was diagnosed with a history of gout for 5 years and was targeted as LSS combined with gouty tophi, and we would like to share this case. In addition, in order to further investigate the deep mechanism of LSS associated with gout, we obtained the intersecting genes of the two diseases based on a machine learning approach by obtaining the dataset GSE113212 related to LSS from the Gene Expression Omnibus (GEO) database, and the genes related to gout from the human gene database. We found that TGFB1, PPARG, and SAMRCC1 may be important biomarkers for treating of both diseases. From a clinical perspective, clinicians should be vigilant about the possibility of gouty lumbar spinal stenosis with tophi in young patients presenting with back pain, hyperuricemia, and elevated inflammatory markers. A combined surgical and pharmacological treatment plan has a favorable prognosis. Investigating the mechanisms of action of core genes may provide new insights for treatment, ultimately leading to the development of comprehensive and personalized diagnostic and therapeutic strategies.